Elucidating local pollution and site representativeness at the Jungfraujoch, Switzerland through parallel aerosol measurements at an adjacent mountain ridge. (26th March 2021) - Bukowiecki, Nicolas; Brem, Benjamin T.; Wehrle, Günther; Močnik, Griša; Affolter, Stéphane; Leuenberger, Markus; Coen, Martine Collaud; Hervo, Maxime; Baltensperger, Urs; Gysel-Beer, Martin
Abstract: Many long-term air pollution and climate monitoring stations face the issue of increasing anthropogenic activities in their vicinity. Furthermore, the spatial representativeness of the sites is often not entirely understood especially in mountainous terrain with complex topographic features. This study presents a 5-year comparison of parallel aerosol measurements (total particle number concentration and equivalent black carbon mass concentration) at the Jungfraujoch in the Swiss Alps (JFJ, 3580 m a.s.l.), and an adjacent mountain ridge, the Jungfrau East Ridge (JER, 3705 m a.s.l.), in 1000 m air-line distance to the main site. The parallel aerosol measurements reveal characteristic differences in the diurnal variations between the two sites under certain specific meteorological conditions. Our analysis estimates that on 20%–40% of the days local activities at the Jungfraujoch have a clear influence on the measured time series of the total aerosol number concentration and the equivalent black carbon mass concentration. This influence is mainly seen in form of strong isolated spikes rather than by an increase in the on-site background concentration. They can thus be flagged during the data quality assurance process and filtered from those measurement parameters available at high time resolution. Removing the spikes from the original time series results in daily mean values for the total aerosol number concentration and equivalent black carbon mass concentration that are 5%–10% lower compared to the original signals. During nighttime with hardly any local pollution sources that cause spikes this percentage decreases towards 0%. The signal baselines at the Jungfraujoch and Jungfrau East Ridge correlate well during more than 50% of the days.